Direct-fed microbials for receiving cattle II: Effects of ProTernative stress formula fed in a dry suspension on growth, feed intake, and health of receiving beef heifers - Siverson, A.V.; Corrigan, M.E.; Higgins, James J.; Blasi, Dale A.; Oleen, Brandon E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Enhanced preconditioning and nutritional management strategies are needed industrywide as a means of controlling stress and related health problems for freshly arrived stocker calves. Direct-fed microbials are feed additives that stimulate natural, nonpathogenic gut flora in an attempt to stimulate competition against potentially pathogenic gut flora. Previous research involving direct-fed microbials offered in a liquid suspension to lightweight stocker calves produced no effects on growth or health performance. Therefore, the objective of our study was to evaluate the effects of a directfed microbial offered as a dry suspension on feed intake, average daily gain, and morbidity of highly stressed beef heifers.
Keywords: Beef; Microbials; ProTernative stress formula; Growth; Feed intake; Health